The Integration of Web-Applications and Collaborative Learning in Mathematics for Grade Five Bhutanese Students - Seldon , Pema; Nipaporn Sakulwongs (Journal of Research and Curriculum Development, 2023)
The purposes of this research are follows: (1) to assess the learning achievement in mathematics among Grade Five Bhutanese students using web-applications and collaborative learning; and (2) to examine the perception of Grade Five Bhutanese students towards web applications and collaborative learning in mathematics. The study was conducted in the 2022 academic year in a lower Secondary school in Bhutan. The population consisted of 31 Bhutanese students from one section of Class Five and they were selected using the cluster random sampling method. This paper presented a mixed-method study incorporating both qualitative and quantitative studies. The research instruments consisted of lesson plans, learning achievement tests (pretest and posttest) and semi- structured interviews. For the quantitative data, learning achievement tests (pretest and posttest) were used and further analyzed using a Paired Sample t-test. The analysis revealed that the mean score of the posttest (14.44) was higher than the mean score of the pretest (10.24) with a mean difference of 4.20. The significance value (p) was also revealed as .01, indicating a statistically significant rise in the posttest scores of the research participants over the pretest scores. Regarding the qualitative data, it was analyzed with semi- structured interviews and conducted on the sample group by dividing the students into six groups. The data collected from the interviews included enthusiastic and motivated responses from the students, revealing positive perception used by the researcher towards intervention in learning mathematics. Thus, all of these findings demonstrated how the integration of web-based applications and collaborative learning in mathematics improved the learning achievement and the perceptions of the students.